2021
DOI: 10.1016/j.xjtc.2021.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Coronary surgery in women: How can we improve outcomes

Abstract: This Invited Expert Opinion is based on the presentation by Dr Jennifer Lawton at the 2021 American Association for Thoracic Surgery Meeting, International Coronary Congress Session. In this opinion, we consider the factors that contribute to the differences in outcomes after coronary artery bypass grafting (CABG) between women and men to provide strategies to optimize outcomes in women.Data to adequately inform coronary artery revascularization in women are limited. The initial data available to inform the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
(116 reference statements)
0
13
0
Order By: Relevance
“…Reducing mortality in women after CABG likely entails a multifactorial approach. 25 The indication to revascularization may have to be different in women compared with men due to the differences in the processes and pathology of coronary artery disease. current diagnostic and therapeutic protocols for coronary revascularization are all informed from data derived from studies performed prevalently in men 21 and may be inadequate for women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing mortality in women after CABG likely entails a multifactorial approach. 25 The indication to revascularization may have to be different in women compared with men due to the differences in the processes and pathology of coronary artery disease. current diagnostic and therapeutic protocols for coronary revascularization are all informed from data derived from studies performed prevalently in men 21 and may be inadequate for women.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing mortality in women after CABG likely entails a multifactorial approach . The indication to revascularization may have to be different in women compared with men due to the differences in the processes and pathology of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing in on ischemic coronary artery disease, women traditionally have had lower rates of coronary artery bypass graft (CABG) surgery compared with men [7 ▪ ]. Mahowald et al showed a higher in-hospital mortality in women undergoing CABG following a myocardial infarction when compared to men even when they were propensity matched [8].…”
Section: Discussionmentioning
confidence: 99%
“…Females have unique CVD risk factors, including gestational diabetes, premature births, autoimmune diseases, and treatment for breast cancer. Though diabetes and depression also affect males, they might be greater risk factors in females than in males [1][2][3]. The earliest data available were based on randomized controlled trials that assessed results only in males [4][5].…”
Section: Introductionmentioning
confidence: 99%